1993
DOI: 10.1128/aem.59.8.2572-2577.1993
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of Agrobacteria to Grape Cells

Abstract: The presence of the Ti plasmid favorably influences the attachment of agrobacteria to grape callus cells, especially during the early stages of a 2-h incubation. Agrobacterium strains attached to a similar extent to both the crown gall-resistant cultivar (Catawba), J'iis labruscana, and the crown gall-susceptible cultivar (Chancellor), Vitis sp. Attachment of the virulent strain to grape callus cells is blocked by the avirulent strain HLB-2 in both the tissue culture cell suspension and the seedling root syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…, 2000) and A. vitis , the causal agent of crown gall in grapevine (Ophel & Kerr, 1990), attach to roots and are very good root colonizers (Brisset et al. , 1991; Pu & Goodman, 1993; Vicedo et al. , 1993; Peñalver et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2000) and A. vitis , the causal agent of crown gall in grapevine (Ophel & Kerr, 1990), attach to roots and are very good root colonizers (Brisset et al. , 1991; Pu & Goodman, 1993; Vicedo et al. , 1993; Peñalver et al.…”
Section: Introductionmentioning
confidence: 99%
“…A more likely reason is that pAtK84b carries genes which are important in early stages of the pathogenic process, e.g., attachment and the potential for competition with or inhibition of pathogens. This possibility is supported by studies which have shown that nopaline-type Ti plasmids enhance attachment (23,29). Alternatively, pAtK84b may enhance chemotaxis to wound sites, as Ti plasmids have been shown to play a role in chemotaxis to wound exudates (1,2).…”
Section: Discussionmentioning
confidence: 93%
“…It is known that a variety of chromosomal genes (chvA, chvB, pscA, and cel genes) are required for attachment of A. tumefaciens to various plant species (Matthysse & McMahan, 1998). However, there is evidence that the Ti plasmid can also contribute to attachment (Pu & Goodman, 1993). It has been previously demonstrated that A. vitis attaches more efficiently than A. tumefaciens to grapevine roots and that pehA, coding for polygalacturonase production by A. vitis, may be associated with attachment (Brisset et al, 1991;Rodriguez-Palenzuela et al, 1991).…”
Section: Discussionmentioning
confidence: 99%